Efficient photon upconversion at remarkably low annihilator concentrations in a liquid polymer matrix: when less is more. Issue 99 (29th November 2018) - Durandin, Nikita A.; Isokuortti, Jussi; Efimov, Alexander; Vuorimaa-Laukkanen, Elina; Tkachenko, Nikolai V.; Laaksonen, Timo
Abstract : A triplet–triplet annihilation upconversion of 24.5% was achieved at a remarkably low 600 μM annihilator concentration in a viscous polymer matrix. Abstract : A green-to-blue triplet–triplet annihilation upconversion of 24.5% quantum yield was achieved at a remarkably low 600 μM annihilator concentration in a viscous polymer matrix. This was made possible by utilizing a ZnTPP-based photosensitizer with exceptionally long 11 ms phosphorescence lifetime. Higher 3 mM annihilator concentration resulted in lower 24% upconversion quantum yield.